KREATIVITAS KEWIRAUSAHAAN DI SEKTOR PARIWISATA: INSPIRASI BAGI MAHASISWA AKADEMI PARIWISATA DENPASAR - Putri, A.A Sagung Ayu Srikandi; I.B. Gde Upadana (Jurnal Kajian dan Terapan Pariwisata, 2024)
Entrepreneurial creativity plays an important role in improving the competitiveness of the global tourism industry. Students as potential talents play a role in designing innovations in the future. This study aims to evaluate entrepreneurial talent development strategies for tourism students in order to optimally contribute to the industry. This qualitative research uses a literature study method. It was found that the appropriate strategies include improving entrepreneurial competencies, project-based learning, and business incubator programs. Business opportunities based on flexibility and technology are worth exploring. Thedevelopment of students' entrepreneurial talents needs to be supported by multi-stakeholder collaboration to accelerate innovation and industry transformation. Continuous evaluation is needed to optimize these strategies.